(untitled) (American Journal of Education and Technology, 2022)
This research made use of a phenomenological approach to understand profoundly the lived experiences of language teachers towards professional development and optimizing their teacher factors. It aimed to highlight the views of English teachers regarding the teacher factor and professional development, the barriers they encounter in English language teaching, and the ways where they could improve themselves as professional teachers. This qualitative study made use of remote interviews via zoom in analyzing the professional development activities employed by English teachers and the other facets connected to them during the school year 2022-2023. Fifteen (15) English teachers teaching in SUCs or Private HEIs were chosen to be the participants of the study. Semi-structured open-ended questions were asked. Data were manually organized and structured from the interviews and thorough scrutiny of themes and identification of essential features were conducted. It was found that teachers’ ongoing reflection, evaluation, and analysis of their own practices are necessary elements of their professional development as these can support them to construct new teaching theories and improve their performances. Therefore, optimizing the teacher factor must be every teacher’s hunger, concern, and intended purpose. Such development does not only depend on formal learning, but it can also be self-initiated by teachers.